2022
DOI: 10.1609/icwsm.v16i1.19351
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Support via Avatar Communication Buffers Harmful Effects of Offline Bullying Victimization

Abstract: Online social support via avatar communication is a powerful tool for bullying victims because they often lack offline social resources. Additionally, avatar communication allows users rich nonverbal interactions (e.g., emotional expressions) while maintaining online anonymity. This study investigates the role of online social support via avatars for victims and how to facilitate such support. Accordingly, we conducted an online questionnaire survey twice on an avatar communication application, Pigg Party, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…We used the logs of users' visits to others' private rooms. We assumed an edge between a visitor and the owner of a room, as in previous work [14,34,35], because visitors tend to be the owner's friends [33]. The dwelling time (s) at over a week were used to represent the weights of the edges (w).…”
Section: Online Social Networkmentioning
confidence: 99%
“…We used the logs of users' visits to others' private rooms. We assumed an edge between a visitor and the owner of a room, as in previous work [14,34,35], because visitors tend to be the owner's friends [33]. The dwelling time (s) at over a week were used to represent the weights of the edges (w).…”
Section: Online Social Networkmentioning
confidence: 99%
“…To construct these networks, we used the logs of users visiting other users' private rooms. As in previous research [2,25,30,31], we established a link between a visitor and the owner of a room because visitors are often friends with the owner [32]. The time spent (in seconds) over a week was used to denote the weights of the links (w).…”
Section: Participants' Neighborsmentioning
confidence: 99%
“…Concerning bullying victims, fewer studies have been undertaken to examine their experience with online support. One of these preliminary efforts is a survey study on online support among victims of offline bullying (Takano & Yokotani, 2022). The study showed that higher online support was related to better global mental health status and fewer symptoms of depression among victims.…”
Section: Perceived Social Support Of Bullying Victimsmentioning
confidence: 99%